Experience- Based Learning to Improve University Studentsâ Competence - Utami, WiwikSri (Proceeding of International Conference on Teacher Training and Education, 2016)
Learning problems are influenced by external and internal factors. External factors includelecturers, materials, interaction patterns, media and technology as well as the learning situation.One of the efforts to overcome learning problems is the improvement of learning which is studentcenteredlearning (student center, learning oriented) to provide a learning experience which ischallenging and fun. Learning innovations also produce a productive creative learning model whichis the combination of collaborative, cooperative and constructive learning. The pattern of learningactivities is through four phases namely orientation, exploration, interpretation and re-creations. Inthe Department of Geography Education, this learning model is chosen with the assumption that itcan provide a learning experience, make students active, creative, responsible and fun.